Q-switched fiber laser operating at 1 μm region with electron beam deposited titanium nanoparticles - Muhammad, Ahmad Razif; Zakaria, Rozalina; Wang, Pengfei; Ahmad, Muhammad Taufiq; Rahim, Hazli Rafis Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (Elsevier, 2019)
We demonstrate the generation of Q-switched pulse train in Ytterbium-Doped Fiber Laser (YDFL) cavity by employing titanium (Ti) thin film as a passive saturable absorber (SA). The Ti-SA was fabricated by depositing Ti particles using electron beam evaporation on the surface of a polyvinyl alcohol (PVA) thin film. Subsequently, a stable Q-switching pulse train was successfully generated by introducing the Ti-SA into a laser cavity. The laser generated a self-starting pulse train with repetition rate that is tunable from 42.96 to 98.12 kHz as the 980 nm pump power is increased from 122.5 mW to 197 mW. At 197 mW pump power, the laser produced a Q-switching pulse train with pulse duration and pulse energy of 3.95 μs and 57.48 nJ, respectively. This demonstration proves that Ti-SA is suitable for generating Q-switched fiber laser. Furthermore, it is easy and cheap to fabricate. © 2019 Elsevier Ltd